A three-tiered approach to investigating patient safety incidents in endoscopy: 4-year experience in a teaching hospital - Berry, Philip; Kotha, Sreelakshmi; Tritto, Giovanni; DeMartino, Sabina (Endoscopy International Open, 2021)
Background and study aims Patient safety incidents (PSIs) in endoscopy, although infrequent, can lead to significant morbidity or mortality. There is no commonly agreed strategy to investigate PSIs. We describe a three-tiered approach to investigation to facilitate appropriate action, shared learning, and timely disclosure to patients as mandated in the UK health system by the Duty of Candor (DoC).Methods PSIs were identified prospectively over a 3-year, 7-month period in a large teaching hospital. Level of investigation was agreed by a group of three senior clinicians. Levels of investigation comprised: 1) rapid desktop review; 2) departmental “mini-root cause analysis” (mini-RCA, developed internally); and 3) hospital-level RCA or mortality review.Results Of 63006 procedures there were 73 reported cases of significant harm. Eleven resulted in death. Thirty PSIs were related to hepatobiliary endoscopy, 17 to lower gastrointestinal endoscopy, and 26 to upper gastrointestinal endoscopy. Hospital-level RCA was performed in six cases, mini-RCA/mortality review in 14, and 53 were examined by the endoscopy lead. Findings were presented in an endoscopy user group (EUG) meeting. There was learning in relation to informed consent, pre-procedural radiology reviews, pre-procedural treatment, escalation planning, teamwork and communication, preparation of equipment, and recognition of delayed complications. Open and honest communication with patients and relatives was facilitated. Conclusions The introduction of an endoscopy-tailored investigation tool, the mini-RCA, as part of a three-tiered approach, facilitated investigation, appropriate action, learning, and disclosure after PSIs.